Making Women Visible: How Gender Quotas Shape Global Attitudes toward Women in Politics - Jessica Kim; Kathleen M. Fallon (Politics & Gender, 2023)
Since the 1990s, gender quotas have been celebrated for improving women's equality. Yet their cross-national and longitudinal impact on attitudes toward female politicians and the mechanism through which this process occurs are not well understood. Using multilevel modeling on 87 nations, we examine how different types of quotas, with varied features and levels of strength, shape beliefs about women in politics. We give particular attention to the mechanism of visibility created by quotas in impacting attitudes. Results suggest that unlike quotas with features facilitating low visibility (i.e., weak quotas), those producing high visibility (i.e., robust quotas) significantly impact public approval of women in politics. However, the direction of this effect varies by quota type. Social context also matters. Robust quota effects—both positive and negative—are especially pronounced in democracies but are insignificant in nondemocracies. Limited differences by gender (men versus women) emerge. Theoretical and policy implications are discussed.
Keywords: 300; gender quotas; public opinion; World Values Survey; exposure; symbolic representation; democracy; gender